2017
DOI: 10.1037/emo0000257
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction contexts bias the perceived expressions of interactants.

Abstract: The present study sought to determine whether contextual information available when viewing social interactions from third-person perspectives, may influence observers' perception of the interactants' facial emotion. Observers judged whether the expression of a target face was happy or fearful, in the presence of a happy, aggressive or neutral interactant. In two experiments, the same target expressions were judged to be happier when presented in the context of a happy interactant, than when interacting with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
2
26
0
1
Order By: Relevance
“…Similarly, visual search facilitation is shown for full body dyads that are positioned to face towardsrather than away fromeach other (Vestner et al, 2018), while facing direction effects are shown to modulate the evaluation of facial emotion of a target face (i.e. the perceived emotional expression of a target face is modulated by the emotion of a simultaneously presented non-target face, but only when positioned to face towards the target; Gray et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, visual search facilitation is shown for full body dyads that are positioned to face towardsrather than away fromeach other (Vestner et al, 2018), while facing direction effects are shown to modulate the evaluation of facial emotion of a target face (i.e. the perceived emotional expression of a target face is modulated by the emotion of a simultaneously presented non-target face, but only when positioned to face towards the target; Gray et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, visual search facilitation is shown for full body dyads that are positioned to face towards – rather than away from – each other (Vestner et al., 2018), while facing direction effects are shown to modulate the evaluation of facial emotion of a target face (i.e. the perceived emotional expression of a target face is modulated by the emotion of a simultaneously presented non-target face, but only when positioned to face towards the target; Gray et al., 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Traditionally, social perception research has focussed on the visual processing of individual faces (Duchaine & Yovel, 2015;Freiwald, Duchaine, & Yovel, 2016), bodies (Peelen & Downing, 2007;Ramsey, 2018), and actions (Blake & Shiffrar, 2007;Cook, Bird, Catmur, Press, & Heyes, 2014). In recent years, however, there has been growing interest in how human observers perceive, attend to, and recall social interactions viewed from third-person perspectives (Gray, Barber, Murphy, & Cook, 2017;Isik, Koldewyn, Beeler, & Kanwisher, 2017;Papeo, Stein, & Soto-Faraco, 2017;Quadflieg, Gentile, & Rossion, 2015). One of the interesting findings to emerge from this new literature is the search advantage for facing dyads.…”
Section: Introductionmentioning
confidence: 99%